Antibacterial activity and mechanism of malondialdehyde against Staphylococcus xylosus and Lactiplantibacillus plantarum isolated from a traditional Chinese dry-cured fish - Zhang, Qi; Jia, Shiliang; Ding, Yicheng; Li, Dongmei; Ding, Yuting; Zhou, Xuxia (Frontiers in Microbiology, 2022)
Malondialdehyde (MDA) is one of the most representative reactive carbonyl species (RCSs) produced by lipid oxidation in food. However, the inhibitory effect of MDA on microorganisms has received little attention. Thus, the aim of this study was to reveal the antibacterial mechanism of MDA on Staphylococcus xylosus and Lactiplantibacillus plantarum isolated from dry-cured fish. The results showed that the minimum inhibitory concentrations (MICs) of MDA on S. xylosus and L. plantarum were 90 µg/mL and 180 µg/mL, respectively. Time-kill curves indicated a concentration-dependent antibacterial activity of MDA. Moreover, cell wall damage, cell membrane depolarization, intracellular adenosine triphosphate (ATP) decline, Ca2+ and Mg2+ leakage, cell morphological destruction and alterations in intracellular biomolecules were observed, which indicated the negative influence of MDA on cell membrane and cellular homeostasis. This study demonstrated the potential antimicrobial properties of MDA and provided theoretical support for the scientific prevention and control of lipid oxidation and microbial contamination in food.